A 125 GeV Higgs and Its Diphoton Signal in Different SUSY Models: A Mini Review. (11th November 2012) - Heng, Zhaoxia
Abstract : In this paper we briefly review our recent studies on a 125 GeV Higgs and its diphoton signal rate in different low-energy supersymmetric models, namely, the minimal supersymmetric standard model (MSSM), the next-to-minimal supersymmetric standard model (NMSSM), the nearly minimal supersymmetric standard model (nMSSM), and the constrained MSSM. Our conclusion is as follows (i) in the allowed parameter space the SM-like Higgs boson can easily be 125 GeV in the MSSM, NMSSM, and nMSSM, while it is hard to realize in the constrained MSSM; (ii) the diphoton Higgs signal rate in the nMSSM and constrained MSSM is suppressed relative to the prediction of the SM, while the signal rate can be enhanced in the MSSM and NMSSM; (iii) the NMSSM may allow for a lighter top squark than the MSSM, which can thus ameliorate the fine-tuning problem.